Tailored covalent organic frameworks by post-synthetic modification - Ding, Huimin; Mal, Arindam; Wang, Cheng (Materials chemistry frontiers, 2020)
Covalent organic frameworks (COFs), constructed by strong covalent bonds based on reticular chemistry, hold great promise in diverse applications. Manipulating COFs with desired functional properties is of paramount significance. However, the standard solvothermal synthetic methodologies for COF synthesis do not always allow direct incorporation of functional groups into frameworks, due to the incompatibility with the building blocks or reaction conditions. In this regard, alternative approaches for post-synthetic modification (PSM) on a pre-established network provide an opportunity for tuning the functional properties of COFs while maintaining a fundamental framework structure. This review describes recent advances and scientific challenges in the area of post-synthetic methodologies to tailor the properties of COFs. Two different major PSM techniques, namely, covalent PSM and post-synthetic metal functionalization, will be discussed. This review describes recent advances and scientific challenges in the area of post-synthetic methodologies to tailor the functionalities and properties of COFs.